Machine Learning Solutions : Expert techniques to tackle complex machine learning problems using Python. - Thanaki, Jalaj (Packt Publishing, 2018)
This book demonstrates a set of simple to complex problems you may encounter while building machine learning models. You'll not only learn the best possible solutions to these problems but also find out how to build projects based on each problem mentioned in the book, with a practical approach and easy-to-follow examples.